Murcia atrial fibrillation project II: protocol for a prospective observational study in patients with atrial fibrillation - José Miguel Rivera-Caravaca; Francisco Marín; María Asunción Esteve-Pastor; Josefa Gálvez; Gregory Y.H. Lip; Vicente Vicente; Vanessa Roldán (BMJ Open, 2019)
Introduction Atrial fibrillation (AF) is characterised by a high stroke risk. Vitamin K antagonists (VKAs) are the most commonly used oral anticoagulants (OACs) in Spain, but their efficacy and safety depend on the time in therapeutic range of International Normalized Ratio (INR) 2.0–3.0 over 65%–70%. Unfortunately, the difficulties of maintaining an optimal level of anticoagulation and the complications of VKAs (particularly haemorrhagic ones), frequently lead to cessation of this therapy, which has been associated with higher risk of adverse events (AEs), including ischaemic stroke. Our aims are as follows: (1) to evaluate the quality of oral anticoagulation with VKAs, the prevalence of poor quality of anticoagulation, and to identify factors predisposing to poor quality anticoagulation; and (2) to identify patients who will stop OAC and to investigate what factors influence the decision of OAC withdrawal.Methods and analysis Prospective observational cohort study including outpatients newly diagnosed with AF and naïve for OACs from July 2016 to June 2018 in an anticoagulation clinic. Patients with prosthetic heart valves, rheumatic mitral valves or valvular AF will be excluded. Follow-up will extend for up to 3 years. During this period, the INR results and changes in the anticoagulant therapy will be recorded, as well as all AEs, or any other information that would be relevant to the proper conduct of research.Ethics and dissemination All patients were informed about the nature and purpose of the study, and the protocol was approved by the Ethics Committee of Hospital General Universitario Morales Meseguer (reference: EST:20/16). This is an observational study focusing on ‘real life’ practice and therefore all treatments and follow-up will be performed in accordance to the routine clinical practice with no specific interventions or visits. The results of our study will be disseminated by presentations at national and international meetings, and publications in peer-reviewed journals.